The Behavioural environment : essays in reflection, application, and re-evaluation - Boal, Frederick Wilgar; Livingstone, David N., 1953-; Kirk, W. (William) (Routledge, 1989)
Placing human action and perception at the centre of the subject, this book considers the effects of mankind on the environment, drawing particularly from William Kirk's work on the behavioural environment model. Reviewing Kirk's original model in light of recent ideological debate and extensive new evidence, this collection of essays from leading names in the field shows that a behavioural approach is essential in understanding human geography and man's relationship with the ecological environment.